A case of herniation of the mylohyoid muscle with penetration of the sublingual gland. Issue 3 (May 2019) - Ishida, Kazuhisa; Kato, Keizo; Inoue, Keisuke; Hatakeyama, Daijiro; Kato, Hiroki; Shibata, Toshiyuki
Abstract: Swelling of the submandibular region is a pathological condition that is frequently encountered in clinical practice. However, the fact that it can result from "sublingual gland herniation, " in which the sublingual gland protrudes from a fissure of the mylohyoid muscle into the submandibular space, is not well known. Here, we report our experience with a case in which swelling of the submandibular region was caused by sublingual gland herniation. The patient visited our hospital with a chief complaint of swelling of the mandibular region. Detailed examination (including ultrasonography, computed tomography (CT), and functional magnetic resonance imaging (MRI) with Valsalva maneuver) confirmed the presence of a fissure in the mylohyoid muscle and protrusion of the sublingual gland into the submandibular space. As a result of no findings indicating inflammation or lymph node swelling including a malignant disease, a follow-up observation was performed. These findings suggested that it was necessary to consider the sublingual gland herniation in a case of submandibular swelling and that echographic and/or MRI examinations combined with the Valsalva maneuever were useful to distinguish.